Dying matters: let's talk about it. (16th September 2010) - Seymour, Jane E; French, Jeff; Richardson, Eve
Abstract : As death has become less common in our daily lives, it has become harder to consider our own mortality or that of those close to us. Lack of openness about death has negative consequences for the quality of care provided to the dying and bereaved. Eradicating ignorance about what can be achieved with modern palliative care and encouraging dialogue about end of life care issues are important means of changing attitudes.